Ingestive behavior of dairy goats fed increasing levels of sugarcane in replacement of corn silage - Lara Canizares, Gil Ignacio [UNESP]; Goncalves, Heraldo Cesar [UNESP]; Rodrigues, Luciana [UNESP]; Marques, Raquel Ornelas [UNESP]; Komiyama, Claudia Marie [UNESP]; Lemos Medeiros, Brenda Batista [UNESP]; Barros Gomes, Helen Fernanda [UNESP]; Machado Franco de Arruda, Guilherme Mendes [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2014)
The objective of this experiment was to evaluate levels of replacement (0, 33, 67 and 100%) of corn silage with fresh sugarcane in dairy-goat diets on the ingestive behavior of these animals. Eight lactating Alpine goats (after lactation peak) with a live weight of 51.95 +/- 3.29 kg were distributed into two 4 x 4 Latin squares according to their milk production. Animals were placed in individual pens where they received diets ad libitum, twice a day, with a roughage: concentrate ratio of 40: 60, during 72 days of experiment. The evaluated variables were time spent feeding (TSF), ruminating (TSR), idle (TSI) and chewing (TSC), dry matter intake (DMI), neutral detergent fiber intake (NDFI), feeding efficiency of dry matter (FEDM) and neutral detergent fiber (FENDF), rumination efficiency of dry matter (REDM) and neutral detergent fiber (RENDF), number of ruminal boli per day (NRB) and number of rumination chews per day (NRC). The different treatments had no effect on TSF or TSR. However, a linear effect was observed on TSC. There was a linear effect on TSI, in which the highest value was observed in the treatment with 0% of sugarcane inclusion. A quadratic effect was observed on dry matter intake, with minimum point of 2.14 kg/day for 68.04% of sugarcane inclusion; however, NDFI was not affected by the different treatments. There was no effect of treatments on FEDM, although a quadratic effect was observed on FENDF, wherein the lowest value was observed in the treatment with 67% of sugarcane inclusion. There was no effect of different levels of corn silage replacement on REDM, RENDF, NRB or NRC. Sugarcane can be replaced with corn silage without changing the times spending on feeding and rumination.
Keywords: Chewing; Feeding; Ruminal bolus; Rumination